Establishment of embryonic shoot–root axis is involved in auxin and cytokinin response during Arabidopsis somatic embryogenesis - Su, Ying Hua; Liu, Yu Bo; Bai, Bo; Zhang, Xian Sheng (Frontiers in Plant Science, 2015)
Auxin and cytokinin signaling participates in regulating a large spectrum of developmental and physiological processes in plants. The shoots and roots of plants have specific and sometimes even contrary responses to these hormones. Recent studies have clearly shown that establishing the spatiotemporal distribution of auxin and cytokinin response signals is central for the control of shoot apical meristem (SAM) induction in cultured tissues. However, little is known about the role of these hormones in root apical meristem (RAM) initiation. Here, we found that the expression patterns of several regulatory genes critical for RAM formation were correlated with the establishment of the embryonic root meristem during somatic embryogenesis in Arabidopsis. Interestingly, the early expression of the WUS-RELATED HOMEOBOX 5 (WOX5) and WUSCHEL (WUS) genes was induced and was nearly overlapped within the embryonic callus when somatic embryos (SEs) could not be identified morphologically. Their correct expression was essential for RAM and SAM initiation and embryonic shoot–root axis establishment. Furthermore, we analyzed the auxin and cytokinin response during SE initiation. Notably, cytokinin response signals were detected in specific regions that were correlated with induced WOX5 expression and subsequent SE formation. Overexpression of the ARABIDOPSIS RESPONSE REGULATOR genes ARR7 and ARR15 (feedback repressors of cytokinin signaling), disturbed RAM initiation and SE induction. These results provide new information on auxin and cytokinin-regulated apical–basal polarity formation of shoot–root axis during somatic embryogenesis.